Doubling farm income through diversification - Singh, Ritu; Kumar, Rakesh (Indian Horticulture, 2019)
At a time when there is a strong perception that farming is not a profitable venture, Shri Satyawan, a farmer from village Daraipur Kalan in Bawana taluk in Delhi, has created waves by earning a profit of about ` 85 lakh a year from 40 acres of land. It is his innovative drive and constant experimentation with multicropping methods that have helped 48-year-old Satyawan to reap a rich harvest. Born in a farm family, he did higher secondary and joined family farming as his life motto. He started his path from farming activities which was depending on traditional method of farming.